ANDALIMAN FRUIT EXTRACT (ZANTHOXYLUM ACANTOPHODIUM) AND IT’S EFFECT ON PREECLAMPSIA AS ANTI-INFLAMMATORY - BARUS, MELVIN NOVA GUNAWANTO; SYAFRUDDINILYAS; SITEPU, MAKMUR; BACHTIAR, ADANG (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study is the first study to test the effect of andaliman on preeclampsia. This study aims to discover whether andaliman fruit extract (Zanthoxylum acanthopodium DC) affects the level of TNF α and IL-6 in preeclamptic LPS Induces mice Methods: This study uses analytical research with quasi-experimental research design in laboratory rats (Micetus Norvegicus) pregnant females given andaliman extract (zantoxylumacantophodium) at doses of 100 mg and 200 mg per day. The study design allowed the researchers to measure the effect of treatment (intervention) in the experimental group by way of comparing the experimental group and control group. This design allows the researcher to determine the extent or extent of the change. The treatment of all samples was carried out simultaneously and during the treatment, it was observed using the type of Postest Only Control Group. Results: Andaliman has been shown to reduce TNF-α levels in preeclampsia mice. The mean TNF-α in the K-, P1, P2 and K+ groups was 84.4; 90.1; 95.1; 109.7 (P<0.001). Andaliman has been shown to reduce IL-6 levels in preeclampsia rats. The mean IL-6 in the K-, P1, P2 and K+groups was 16.7; 67.5; 18.8; 21.1 (P<0.001). Conclusion: This study proves that there are anti-inflammatory effects possessed by the extract of Andaliman (Zanthoxylum acanthopodium), thus showing a decrease in proinflammatory cytokine levels, namely TNF-α, IL6. This study also has a good clinical outcome after administering Andaliman extract (Zanthoxylum acanthopodium), where there are improvements in blood pressure, cystole-diastole, MAP and decreased urinary protein in research subjects with preeclampsia.